2019
DOI: 10.1002/chem.201903719
|View full text |Cite
|
Sign up to set email alerts
|

Adduct of NacNacAl with Benzophenone and Its Coupling Chemistry

Abstract: Reaction of NacNacAl (NacNac=[DippNC(Me)CHC(Me)NDipp]−) with one equivalent of benzophenone affords a ketylate species NacNacAl(η2(C,O)‐OCPh2) that undergoes easy cyclization reactions with unsaturated substrates. The scope of substrates included benzophenone, aldimine (PhNC(Ph)H), quinoline, phenyl nitrile, trimethylsilyl azide, and a saturated cyclic thiourea. The latter substrate reacted by an unusual C−N cleavage that left the C=S functionality intact. The new products were characterized by NMR spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 32 publications
4
25
0
Order By: Relevance
“…In previous work, we reported that the benzophenone complex 3 reacts with quinoline to give the C−C coupling product 4 (Scheme 1). [14] We have now established that reaction of the Al I compound 1 with a mixture of benzophenone and pyridine gives chemoselectively the analogous coupling product 5 (Scheme 2). This result is significant because 1 instantaneously reacts with both of these substrates independently: in the case of benzophenone it affords the adduct 3 or pinacolate NacNacAl(OCPh 2 ) 2 (if two equivalents of benzophenone are used), and with pyridine it gives a red gel of unknown composition [8b] .…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…In previous work, we reported that the benzophenone complex 3 reacts with quinoline to give the C−C coupling product 4 (Scheme 1). [14] We have now established that reaction of the Al I compound 1 with a mixture of benzophenone and pyridine gives chemoselectively the analogous coupling product 5 (Scheme 2). This result is significant because 1 instantaneously reacts with both of these substrates independently: in the case of benzophenone it affords the adduct 3 or pinacolate NacNacAl(OCPh 2 ) 2 (if two equivalents of benzophenone are used), and with pyridine it gives a red gel of unknown composition [8b] .…”
Section: Resultsmentioning
confidence: 92%
“…[20] Furthermore, with oxidizing bases,s uch as quinoline, reaction with 1 resultsi nt he CÀCc oupling of heterocycles. [14] But al ess oxidizing andm ore basic heterocycle such as DMAP, leads to backboned eprotonation. [8b] It becomes,c lear that for fenchone, which can be regarded as aw eak but oxidizing base, the main mode of reactivity with Al I is charget ransfer to the carbonyl moiety,l ikely creatingabiradicaloid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there has been no prior example of such a coupling on a single carbenoid center. Nevertheless, the chemistry outlined in Scheme is somewhat reminiscent of the coupling of quinoline with the benzophenone adduct NacNacAl(η 2 (C,O)‐O=CPh 2 ), which results in C−C bond formation at the 2‐position of the quinoline . It further suggests that a charge transfer from the electron‐rich Al I species 1 to an N‐heterocycle and/or formation of a singlet biradical species may be responsible for the chemistry illustrated in Scheme and Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…The chemistry of 2 , in particular, is undergoing a recent renaissance, being a key reagent in a number of recent publications [12] . These recent reports include the activation of small molecules (CO, C 2 H 4 ), [12c,j] reduction chemistry (including that of benzene), [12b,e,i,k,m] cycloadditions [12a,d,g] and various bond activations including C−H and C−F [12c,f,h,l,n] . The vast majority of the reactions of 1 and 2 are best described as oxidative additions, although some evidence of nucleophilic behaviour has been reported (especially with electropositive metals/Lewis acids) and this has been exploited in the formation of Al‐metal donor/acceptor bonds [11] .…”
Section: Introductionmentioning
confidence: 99%